The Effects of Pot Sizes and Number of Plants per Pot on the Growth of Amorphophallus muelleri Blume - Yoko Mine (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2010)
To determine the effects of pot sizes and the number of plants per pot on the growth of Amorphophallus muelleri, seed corms weighing 100-125 g were planted in polyethylene pots. In the first experiment, a corm was planted in pots containing various amounts of growth media: i.e., 0.25, 0.40, 0.50, 1.00, 1.33, 2.00 and 4.00 kg. In the second experiment, different numbers of plant, i.e., 1, 2, 3, 4 and 5, were grown in pots containing 4.00 kg of growth media. When plants were grown in pots containing a small amount of media (1.33 kg pot–1 or less), they produced small daughter corms and entered dormancy earlier than usual. The number of plants per pot had little effect on corm weight if the amount of growth media per plant was 0.80 kg or greater. As a result, corm yield increased with an increase in the number of plants per pot. The period from corm planting to harvest was slightly longer when only one plant was grown in a pot than when 2–5 plants were grown in the same-sized pot. This study suggested that the low productivity of A. muelleri in shallow soil was associated not only with a small amount of soil per plant but also with limited rooting volume. Keywords: available water, competition, dormancy, plant density, soil depth